Einleitung zum Themenheft Authentizität zwischen Wahrhaftigkeit und Inszenierung? - Felder, Ekkehard; Gardt, Andreas (Linguistik Online, 2020)
The central question of this issue Authenticity between Truthfulness and Pretension? is directly related to the epistemologically explosive alternative of Reality or Construction?, which is the subject of an anthology published in 2018 under the same title (Felder/Gardt 2018). While the volume Reality or Construction dealt with interdisciplinary aspects with regard to the question of whether we actually have access to reality or whether we are merely caught up in our own constructions of reality, the present issue is concerned with a decidedly linguistic approach (more precisely: an approach based on the analysis of discourse and conversation, the history of concepts and relationships as well as social history), which also includes aspects of social symbolism and social semiotics. The articles focus on the phenomenon of authenticity, which opens up the speaker-centred perspective of truthfulness to complement the world-related issue of reality.